2006
DOI: 10.1063/1.2189933
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of nanoparticle suspensions

Abstract: We describe an optical beam deflection technique for measurements of the thermal diffusivity of fluid mixtures and suspensions of nanoparticles with a precision of better than 1%. Our approach is tested using the thermal conductivity of ethanol-water mixtures; in nearly pure ethanol, the increase in thermal conductivity with water concentration is a factor of 2 larger than predicted by effective medium theory. Solutions of C 60 -C 70 fullerenes in toluene and suspensions of alkanethiolate-protected Au nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
129
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(146 citation statements)
references
References 48 publications
10
129
1
6
Order By: Relevance
“…The same year dispersed multiwall carbon nanotubes (MWCNT) in water measuring an enhancement up to 160% at only 1% volume fraction of MWCNT. From this moment, there have been many studies in three kinds of nanoparticles dispersed in heat transfer fluids, namely metallic particles as aluminum (Al) (Murshed et al, 2008) and gold (Au) (Putnam et al, 2006), CNT Segarra et al, 2013;Xie et al, 2003), and non-metallic particles as silica (SiO 2 ), alumina (Al 2 O 3 ) and titania (TiO 2 ) (Murshed et al, 2005). The convective heat transfer coefficient has been also studied Kim et al, 2009a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The same year dispersed multiwall carbon nanotubes (MWCNT) in water measuring an enhancement up to 160% at only 1% volume fraction of MWCNT. From this moment, there have been many studies in three kinds of nanoparticles dispersed in heat transfer fluids, namely metallic particles as aluminum (Al) (Murshed et al, 2008) and gold (Au) (Putnam et al, 2006), CNT Segarra et al, 2013;Xie et al, 2003), and non-metallic particles as silica (SiO 2 ), alumina (Al 2 O 3 ) and titania (TiO 2 ) (Murshed et al, 2005). The convective heat transfer coefficient has been also studied Kim et al, 2009a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The surface charge is one of the primary factors controlling nanoparticle aggregation. Furthermore, Cahill and collaborators 13 demonstrated that nanofluids exhibiting good dispersion do not show any unusual enhancement of thermal conductivity.…”
mentioning
confidence: 99%
“…Nanometer-sized stable metal, metal oxides or carbon particles in various forms could be suspended in the industrial heat transfer fluids (water and organic liquids), and can result in anomalously large enhancements of the thermal conductivities. [1][2][3][4][5] These reports show that only 5 vol. % of nanoparticles such as alumina (Al 2 O 3 ), copper oxide (CuO), and copper (Cu) dispersed in different base fluids, the thermal conductivity of the nanofluids was observed a significant improvement ($60%) as compared to the corresponding base fluids.…”
Section: Introductionmentioning
confidence: 99%